The Phenomenon of Waterlogging Due to Poor Drainage in the Tanjung Duren Area, West Jakarta - Miftahudin , Miftahudin; Marsya Luna Lestari; Tri Susanto; Salsabila Ahadini Nurahmat; Williamzu Williamzu; Darmawan Listya Cahya (Journal of Engineering, Electrical and Informatics, 2025)
Tanjung Duren in West Jakarta is a dense urban area with a high level of development and activity, which has an impact on increasing waterproofing surfaces and decreasing drainage capacity. This research aims to identify the main causes of inundation, evaluate the performance of drainage systems, and formulate ap-plicable technical and non-technical solutions. A mixed-method approach was used, including field ob-servations at inundation points, technical measurements of channels, citizen perception surveys, and semi-structured interviews. The results showed that clogging by garbage, inappropriate channel cross-sections, and poor drainage connectivity were the main causes of inundation. The impact of in-undation includes mobility disruptions, economic losses, and health risks to residents. Hydrologi-cal-hydraulic analysis showed a mismatch between runoff discharge (Qin) and channel capacity (Qcap), with a ratio value of ρ ≥ 1 at some points. The proposed solutions consist of routine cleaning, increasing channel capacity, implementing infiltration wells, and strengthening community participation. Recom-mendations also include the establishment of a local taskforce and a waste management education pro-gram. This research emphasizes the importance of an integrated approach based on data and cross-sectoral collaboration in sustainable urban drainage management.